Demonstration of Rhodes grass (Chloris gayana Kunth) varieties at selected highland and midland agro-ecologies of Guji zone, Oromia, Ethiopia - Basha Kebede; Tekle Bobo (Global Journal of Ecology - Peertechz Publications, 2023)
Guji zone has different agro-ecologies suitable for livestock production. However, grazing land was shrinking for the production of feed which is the most pre-request for livestock production. As a result, farmers used pasture and crop residues which are insufficient and not available during the dry season. Hence, there was a feed shortage at different agroecologies. Rhodes grass is used as livestock feed, soil, and water conservation but improved Rhodes grass varieties were not intensively produced by farmers and hence feed shortage is affecting the supply of livestock products for household consumption. Improved Rhodes grass is the possible solution for feed shortage due to it is intensively harvested throughout the year and ensures feed availability for livestock. Therefore, a demonstration of Rhodes grass is needed on a farmer's field. The objective of this study was to evaluate the performance of Rhodes grass on farmers' plots. Adola Rede (midland agroecology) and Ana Sora (highland agroecology) were selected based on their livestock and Rhodes grass production potential. Masaba and ILRI-7384 Rhodes grass varieties were demonstrated on a 50 m2 plot area. Descriptive statistics were used to analyze the data. Accordingly, the Masaba variety was highly performed in plant height (108.6 cm), fresh biomass (4.24t/ha), and survival rate (83.4%) than ILRI-7384 accession at both agroecologies. Except in seed yield at the highland area in all traits, the Masaba variety was well performed than ILRI-7384. The result of one-way ANOVA revealed that across agroecology fresh biomass yield and survival rate of Masaba was a statistically significant difference at 10% and 5% respectively. Farmers liked to produce Rhode grass varieties. Fresh biomass and survival rate was important trait obtained from the Masaba variety in both agro-ecologies. Thus, the Masaba variety was recommended for livestock feed at highland and midland agro-ecologies of the Guji zone.